2013
DOI: 10.1177/1362168813505381
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of planning language objectives in content-based ESL instruction

Abstract: The purpose of this research was to investigate the major patterns in content-based instruction (CBI) lesson plans among practicum teachers at the final stage of an MA TESOL program. One hundred and seven lesson plans were coded according to a typology developed to evaluate clarity and identify areas of potential difficulty in the design of content and language objectives by TESOL teacher candidates for use in PreK–12 ESL classrooms. Participants in our study tended to have more difficulty in designing languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 36 publications
6
61
0
Order By: Relevance
“…It contains both a language subject and a content course (Kiziltan & Ersanh, 2007). In order to efficiently launch and guide oral teaching, Baecher, Farnsworth, and Ediger (2014) underlines the idea that language teachers should be familiar with the relevant knowledge of specialized courses, which is, undeniably, a challenge to language instructors. By choosing different kinds of teaching techniques to demonstrate new words and expressions, it is particularly essential for both language teachers and content teachers to build teamwork in the actual operation.…”
Section: Adjunct Language Instruction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains both a language subject and a content course (Kiziltan & Ersanh, 2007). In order to efficiently launch and guide oral teaching, Baecher, Farnsworth, and Ediger (2014) underlines the idea that language teachers should be familiar with the relevant knowledge of specialized courses, which is, undeniably, a challenge to language instructors. By choosing different kinds of teaching techniques to demonstrate new words and expressions, it is particularly essential for both language teachers and content teachers to build teamwork in the actual operation.…”
Section: Adjunct Language Instruction Modelmentioning
confidence: 99%
“…Teachers should select certain acceptable, accessible and comprehensible materials for students (Baecher et al, 2014 When doing the business English language previewing, students may improve their own listening, speaking, reading, writing and translating skills through WeChat. Diagram 2 below reveals how student-centered diverse language skills assist business content learning through WeChat.…”
Section: Previewing and Online Learning Stagementioning
confidence: 99%
“…There are two particular aspects of language teaching which might account for the difficulties noted by Baecher et al. (). These are the issues of content‐based language teaching (Crandall, ; Lyster & Ballinger, ) and teacher language awareness (Andrews, ).…”
Section: Review Of the Lesson‐planning Literature In Curriculum Studiesmentioning
confidence: 99%
“…Baecher et al. () observe, however, that the balance between content and language is a difficult one to achieve, and Creese () suggests that the default position is to prioritize learning subject matter over language.…”
Section: Review Of the Lesson‐planning Literature In Curriculum Studiesmentioning
confidence: 99%
“…Dale and Tanner (2012) see developing learners' vocabulary as a key concern for CLIL teachers as they move into what they describe as 'phase 2' in teacher development. This is a crucial concern, as it is increasingly being found that content teachers in immersion or CLIL contexts struggle to find ways of balancing a focus on content and language (Baecher, Farnsworth, and Ediger 2014;Cammarata and Tedick 2012;Tan 2011). Understanding the interactional practices of content teachers as they manage shifts of focus to aspects of language (in this case vocabulary) has important implications for the development in the context of CLIL of what Walsh (2012) calls 'classroom interactional competence' -the understanding and practical skill required by teachers to use language and interaction in ways that promote learning opportunity.…”
Section: Introductionmentioning
confidence: 99%